Asocijativna snaga i čestota za 228 imenskih kolokacija u hrvatskom jeziku - Ordulj, Antonia; Žauhar, Valnea (2018)
Istraživanja kolokacijske kompetencije u hrvatskom kao materinskom (Ordulj i Cvikić 2017) i inom jeziku (Ordulj 2016) pokazuju kako na znanje imenskih kolokacija kod izvornih i neizvornih govornika, uz morfološku obilježenost, utječu čimbenici čestotnosti te asocijativne snage kolokacijskih sastavnica. Upravo je zato cilj ovoga rada prikazati podatke o asocijativnoj snazi i čestoti kolokacijskih sastavnica za 228 kolokacija osnovnoga tipa sa strukturom pridjev+imenica. Podaci o asocijativnoj snazi prikupljeni su na uzorku izvornih govornika hrvatskoga jezika (N=283). Ispitanici su koristeći numeričku skalu procjenjivali stupanj međusobne asocijacije ili povezanosti pridjeva i imenice koji čine kolokaciju. Podaci o čestotnosti za pojedinu kolokaciju dobiveni su korpusnom analizom u korpusu hrWaC 2.1
Research on collocational competence in Croatian as L1 (Ordulj and Cvikić 2017) and Croatian as second and foreign language (Ordulj 2016) has shown that the knowledge of noun collocations of native and non-native speakers is affected not only by morphological markedness, but also by the frequency and associative strength of collocation components. Since no standardised data on the associative strength of collocational components in the Croatian language are available, the aim of this paper is to examine the data on the associative strength and frequency of collocation components for 228 collocations which have a basic adjective-noun structure, and to supplement the existing collocational dictionary that illustrates frequency (Ordulj 2016) with information about associative strength. The data on collocational associative strength were gathered from a sample of 283 native speakers of Croatian. By using a numerical scale, respondents evaluated the degree of association or connectedness of adjectives and nouns in collocations. The frequency data for particular collocations were gathered on the basis of corpus analysis of the hrWaC 2.1 corpus (Croatian Web Corpus - Ljubešić and Erjavec 2011). This analysis of the frequency and associative strength of noun collocations will provide a better insight into the psychological and linguistic characteristics of colocations which are used in research on collocational competence in Croatian as L1 and Croatian as Second and Foreign Language (L2). Furthermore, this study will provide experts and teachers with a more systematic insight into the analysis of lexical bonds in Croatian and enable them to make more adequate choices of examples for practicing collocational competence in Croatian as L2.
Bibliografija: str. 85-89.
Sažetak ; Summary.
Keywords: Asocijativna lingvistika -- Hrvatski jezik -- Imenske kolokacije